Cr-Doped Li2ZnTi3O8 as a High Performance Anode Material for Lithium-Ion Batteries - Zeng, Xianguang; Peng, Jing; Zhu, Huafeng; Gong, Yong; Huang, Xi (Frontiers in Chemistry, 2021)
Li2ZnTi2.9Cr0.1O8 and Li2ZnTi3O8 were synthesized by the liquid phase method and then studied comparatively using X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), galvanostatic charge–discharge testing, cyclic stability testing, rate performance testing, and electrochemical impedance spectroscopy (EIS). The results showed that Cr-doped Li2ZnTi3O8 exhibited much improved cycle performance and rate performance compared with Li2ZnTi3O8. Li2ZnTi2.9Cr0.1O8 exhibited a discharge ability of 156.7 and 107.5 mA h g−1 at current densities of 2 and 5 A g−1, respectively. In addition, even at a current density of 1 A g−1, a reversible capacity of 162.2 mA h g−1 was maintained after 200 cycles. The improved electrochemical properties of Li2ZnTi2.9Cr0.1O8 are due to its increased electrical conductivity.